2010
DOI: 10.4103/0378-6323.69066
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis in infants and children in India

Abstract: Atopic dermatitis (AD) is a chronic relapsing eczematous skin disease characterized by pruritus and inflammation and accompanied by cutaneous physiological dysfunction, with a majority of the patients having a personal or family history of "atopic diathesis." The term "atopic diathesis" refers to the presence of allergic rhinitis, bronchial asthma or AD. The universal occurrence of AD is no longer debated. However, published material about its natural history, etiopathogenesis, epidemiology, clinical patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 15 publications
1
24
1
1
Order By: Relevance
“…It was also seen that 32.6% (14) of the cases with flare ups between 4 and 6 had mild severity while only 16.7% of cases with flare ups greater than 7 in the past one year had mild disease, which in turn points to an increase in Dhar et al reported a personal history of atopy in 18.5% patients; a history of allergic rhinitis was present in 12.3% and bronchial asthma in 4.7%. 15 In the present study, 48% of the cases had history of atopy, of which allergic rhinitis and bronchial asthma showed a prevalence of 32% and 24% respectively and both are higher than what observed in the above study. While trying to find a relation between history of atopy and severity of the disease, it was seen that 18% (5) case of allergic rhinitis had mild disease while 39.5% (19) of the cases had it of moderate severity.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It was also seen that 32.6% (14) of the cases with flare ups between 4 and 6 had mild severity while only 16.7% of cases with flare ups greater than 7 in the past one year had mild disease, which in turn points to an increase in Dhar et al reported a personal history of atopy in 18.5% patients; a history of allergic rhinitis was present in 12.3% and bronchial asthma in 4.7%. 15 In the present study, 48% of the cases had history of atopy, of which allergic rhinitis and bronchial asthma showed a prevalence of 32% and 24% respectively and both are higher than what observed in the above study. While trying to find a relation between history of atopy and severity of the disease, it was seen that 18% (5) case of allergic rhinitis had mild disease while 39.5% (19) of the cases had it of moderate severity.…”
Section: Discussioncontrasting
confidence: 54%
“…[21][22][23] An open-pilot study conducted in India by Dhar et al in which patients were advised to strictly adhere to a diet excluding milk and milk products, nuts and nutcontaining foods, egg and egg-containing foods, sea fish and prawns, brinjal and soyabean for a period of 3 weeks, showed a statistically significant reduction in severity scores after dietary elimination alone. 15 A study conducted by Sloper et al, at London offering a food elimination diet concluded that a standard elimination diet avoiding cows' milk, egg, tomatoes and possibly colours and preservatives will help up to three-quarters of patients, and this diet may be considered in all children with moderate or severe eczema. 24 A recent cochrane review of nine randomized controlled trials of food allergy in patients with AD showed that there appears to be no benefit of an egg and milk-free diet in unselected participants with atopic eczema.…”
Section: Discussionmentioning
confidence: 99%
“…There is increased colonization of the eczematous and/or uninvolved skin of atopic dermatitis patients by Staphylococcus aureus. [1][2][3] Reports suggest that the emergence of community acquired-methicillin resistant Staphylococcus aureus strains in the general population could pose new challenges in atopic dermatitis. [4,5] Nevertheless, limited data is available regarding the proportion of patients colonised with methicillin-resistant Staphylococcus aureus (MRSA) in pediatric atopic dermatitis.…”
Section: Introduction Introductionmentioning
confidence: 99%
“…The incidence has been found to be higher among the new immigrants to the industrialized countries. [16] The reduced exposure to bacterial and parasitic infections in childhood leads to an abnormal development of the immune system, which tends to over react to relatively innocuous antigens-hygiene hypothesis. A study comparing the severity of AD in Indian children in the UK or US and in India revealed a less-severe form of the disease in children born and brought up in India.…”
Section: Majority Of the Patients In A Study By Sarkar Andmentioning
confidence: 99%